The widow - Neggers, Carla (Don Mills, Ont. : Mira, 2006)
Homicide detective Abigail Browning, still seeking answers about her husband's death seven years earlier, follows an anonymous tip back home to Maine, where she teams up with search-and-rescue worker Owen Garrison to unravel this mystery.
Keywords: Widows -- Fiction; Women detectives -- Fiction; Murder -- Investigation -- Fiction; Mount Desert Island (Me.) -- Fiction; Romantic suspense fiction